A dipodal bimane–ditriazole–diCu(ii) complex serves as an ultrasensitive water sensor. Issue 16 (2nd February 2022) - Karmakar, Joy; Pramanik, Apurba; Joseph, Vincent; Marks, Vered; Grynszpan, Flavio; Levine, Mindy
Abstract : A bimane ditriazole–copper(ii ) complex serves as an ultrasensitive water sensor. Key features of the system also include rapid response times and good selectivity for water compared to other protic solvents. Abstract : An ultrasensitive fluorescent water sensor based on a dipodal bimane–Cu(ii ) complex is reported here. This complex, which is non-fluorescent in the absence of water, demonstrates a remarkable turn-on fluorescence in the presence of extremely low (0.000786% v/v) concentrations of water, via highly selective water-induced displacement of copper and restoration of the innate bimane fluorescence.